PEMBERIAN KITOSAN DAN PENGARUHNYA TERHADAP BERAT BADAN DAN KADAR TRIGLISERIDA DARAH TIKUS SPRAGUE-DAWLEY YANG DIBERI PAKAN ASAM LEMAK TRANS - Ali, Abdurrahman; Amalia, Leily; Suptijah, Pipih (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2015)
ABSTRACTThis study was aimed to analyze the effects of chitosan intake on body weight and plasma triglyceride level in Sprague-dawley rats fed by trans fatty acid. This study was an experimental on animal using factorial randomized with post-test only control group design. The samples were 28 male Sprague-dawley rats aged two months old. The samples were divided into one control (K) and three treatment groups which received chitosan as much as 0.035 g (P1), 0.045 g (P2), and 0.055 g (P3). The feed was high-fat diet, namely added by melted margarine as a source of trans fatty acid, as much as 1.7 g per day. Intervention was done for 14 and 28 days. Measurement of body weight was done every three days, whereas measurement of triglyceride level was done after 14 and 28 days intervention. The study revealed that feeding of melted margarine in a dose of 1.7 g per day increased body weight of control group as much as 54% after 28 day intervention. The increase was higher than P1, P2, and P3 groups which were elevated by 48.7%, 27.8%, and 38.9% respectively. In addition, after 14 day intervention, the plasma triglyceride levels of control and P1 groups were categorized as hypertriglyceridemia, namely 254.3±49.0 mg/dL and 241.7±58.5 mg/dL respectively. In the meanwhile, the plasma triglyceride levels of P2 (128.3±14.3 mg/dL) and P3 (141.3 ± 25.3) were significantly lower than the control and P1 groups. After 28 day intervention, there is no significant difference on plasma triglyceride level among groups (p>0.05), but the triglyceride level of each group was significantly lower than the levels after 14 day intervention (p<0.05).Keywords: body weight, chitosan, trans fatty acids, triglycerideABSTRAKPenelitian ini bertujuan menganalisis pengaruh pemberian kitosan terhadap berat badan dan kadar trigliserida plasma tikus Sprague-dawley yang diberi pakan asam lemak trans. Penelitian ini merupakan experimental study pada hewan percobaan, menggunakan rancangan kelompok faktorial dengan post test only control group. Sampel penelitian adalah 28 ekor tikus Sprague-dawley jantan berusia dua bulan, dikelompokkan menjadi satu kelompok kontrol (K) dan tiga kelompok perlakuan (P) dengan penambahan kitosan 0,035 g (P1), 0,045 g (P2), dan 0,055 g (P3) dalam diet yang diberikan. Pakan merupakan diet tinggi asam lemak trans, yaitu dengan penambahan margarin yang dipanaskan sebanyak 1,7 g per hari. Intervensi dilakukan selama 14 dan 28 hari. Berat badan ditimbang setiap tiga hari sementara pengukuran kadar trigliserida dilakukan setelah 14 dan 28 hari perlakuan. Penambahan margarin 1,7 g per hari menjadikan berat badan tikus kelompok kontrol (tanpa kitosan) meningkat 54% setelah 28 hari intervensi, lebih tinggi dibandingkan kelompok P1, P2, dan P3 yang masing-masing mengalami kenaikan berat badan 48,7%, 27,8%, dan 38,9%. Setelah 14 hari intervensi, kadar trigliserida plasma tikus kelompok kontrol dan P1 mengalami hipertrigliseridemia, yaitu masing-masing 254,3±49,0 mg/dL dan 241,7±58,5 mg/dL. Sementara itu, kadar trigliserida plasma tikus kelompok P2 (128,3±14,3 mg/dL) dan P3 (141,3 ± 25,3) lebih rendah dan berbeda signifikan dibandingkan kelompok kontrol dan P1. Setelah 28 hari intervensi, kadar trigliserida plasma tikus tidak menunjukkan perbedaan signifikan antar kelompok (p>0,05), tetapi menunjukkan hasil yang lebih rendah dan berbeda signifikan dibandingkan kadar trigliserida setelah 14 hari (p<0,05).Kata kunci: asam lemak trans, berat badan, kitosan, trigliserida